Environmental Factors Related to Diarrheal Disease in the Work Area of ​​the Payung Sekaki Pekanbaru Health Center (HEALTH CARE: JURNAL KESEHATAN, 2025)
Diarrheal disease is a public health problem in Indonesia, characterized by high morbidity and mortality rates, especially in toddlers. In 2024, there were 145 cases of diarrhea in toddlers in the working area of the Payung Sekaki Health Center in Pekanbaru City. An unhealthy environment is one of the risk factors that can increase the incidence of diarrhea in toddlers. This study aims to determine the relationship between environmental factors and the incidence of diarrhea in toddlers. Methods: This study is quantitative analytical using a cross-sectional design with a sample of 50 mothers from a total of 315 mothers who have toddlers as the population. The sample was selected by non-probability sampling with a purposive sampling method, and the data were analyzed using univariate and bivariate with the chi-square test. Results: The study showed that there was a significant relationship between several environmental factors with the incidence of diarrhea in toddlers, namely the availability of toilets (p = 0.003), how to store food (p = 0.017), how to provide drinking water (p = 0.012), hand washing habits (p = 0.002) and how to dispose of feces (p = 0.000). The clean water source factor was found to be not significantly related (p = 0.127) to diarrhea in toddlers. Conclusion: Environmental factors, namely the availability of toilets, how to store food, how to provide drinking water, hand washing habits and how to dispose of feces are related to diarrhea in toddlers.